Tungsten Inert Gas Welding of Al-Mg Alloys With and Without Scandium Addition (Journal of Informatics and Mathematical Sciences, 2018)
In this study, a comparative evaluation of Tungsten Inert Gas (TIG) welding on two different alloys, one with the addition of rare earth metal Scandium and the other alloy without the addition of scandium was undertaken. The Innovative Recycled Cast Al-Mg-Sc alloy has been prepared using Vacuum Induction Melting Casting Furnace, which is available in India and the TIG welding process was applied over it. Microstructural examination revealed that both welds contain shrinkage voids and porosity in the weld zone. Brittle dendrites formed in the wrought alloy without scandium reduces the yield stress to a very low level. Very fine grains formed in the cast Al-Mg-Sc alloy TIG welded joint and the nature of non-dendritic grains formed are responsible for the enhancement of yield stress. The weld tensile properties of cast scandium added aluminum-magnesium alloy plates were found out to be better than the wrought alloy plate. These results clearly show that Cast Al-Mg-Sc alloy compared to Wrought AA5083-H321 alloy is good for industrial applications.
Keywords: Tungsten inert gas welding; AA5083-H321 alloy; Scandium; Tensile properties